2020
DOI: 10.1111/imj.14652
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic stroke and transient ischaemic attack on anticoagulants: outcomes in the era of direct oral anticoagulants

Abstract: Clinical and imaging characteristics of patients receiving direct oral anticoagulants presenting with transient ischaemic attack or stroke are lacking. A retrospective review of all patients who presented to a high-volume primary stroke centre with acute stroke symptoms while prescribed an oral anticoagulant between January 2012 and June 2017. Clinical, radiological characteristics and functional outcomes were examined. Anticoagulated patients diagnosed with stroke or transient ischaemic attack shared similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Qi deficiency, blood stasis and heat toxicity are important factors influencing the occurrence of disease (Xu et al, 2018). The relationship between the syndrome components of the combination analysis found that the cerebral ischemic factor was the most common syndrome of qi deficiency and turbidity (Valente et al, 2018). Western medicine believes that the pathogenesis of cerebral ischemic diseases is complex, including inflammation, cell damage amongst others (Zou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Qi deficiency, blood stasis and heat toxicity are important factors influencing the occurrence of disease (Xu et al, 2018). The relationship between the syndrome components of the combination analysis found that the cerebral ischemic factor was the most common syndrome of qi deficiency and turbidity (Valente et al, 2018). Western medicine believes that the pathogenesis of cerebral ischemic diseases is complex, including inflammation, cell damage amongst others (Zou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of ischemic cerebrovascular events within 12 months of enrollment, including transient ischemic attacks (TIAs) and AIS, was monitored. [8][9][10]…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…Across recent pooled international data, 22.5% of patients who had an ischaemic stroke had been receiving anticoagulant therapy prior to stroke onset, with approximately 13% on DOACs and 72% on warfarin 4 . We previously showed that over a 5‐year period from 2012 to 2017, one third of warfarinised patients with acute stroke were thrombolysed due to subtherapeutic international normalised ratio (INR) levels on presentation (INR ≤ 1.7) compared to only 1 out of the 19 patients taking DOACs who had received thrombolysis 5 . The lack of acute DOAC‐level testing was identified as one of the potential barriers to providing intravenous thrombolysis to patients presenting with stroke while on DOACs.…”
Section: Doac N (%) or Median (Iqr) Combined (N = 195) Apixaban (N =...mentioning
confidence: 99%
“…4 We previously showed that over a 5-year period from 2012 to 2017, one third of warfarinised patients with acute stroke were thrombolysed due to subtherapeutic international normalised ratio (INR) levels on presentation (INR ≤ 1.7) compared to only 1 out of the 19 patients taking DOACs who had received thrombolysis. 5 The lack of acute DOAC-level testing was identified as one of the potential barriers to providing intravenous thrombolysis to patients presenting with stroke while on DOACs. This may be further attributed to the lack of awareness of such assays by front-line clinicians, perceived delays to decision-making and the limited Conflict of interest: None.…”
mentioning
confidence: 99%